전자기장을 이용한 준설토 고효율 이송기술 실증 및 기술 지침 개발 - 김동철(Dong-Chule Kim); 김유승(Yu-Seung Kim); 여찬수(Chan-Su Yea); 김선빈(Sun-Bin Kim); 박승민(Seung-Min Park) (한국연안방재학회지, 2018)
As the research about increasing the efficiency of dredging soil transport, the technology ,which reduce the friction between pipe wall and fluid in the pipe and disturbed generating pipe blockage, has been developed. So for the purpose of applying this technology to real construction site, main test has been tried at the real scale test in field. As a test result, this paper will show 30% flow efficiency increasing by permitted electro magnetic force to the pipe. And test result was evaluated as a ultra sonic velocity profiler. To propose the design technique and the execution manual of the high efficiency dredging material transport technic, this research have confirmed flow status changing depending on a soil material kind under electro-magnetic field and analyze the effect of electro-magnetic field which affects to each dredged soil material transportation. For achieving this research, EMF(Electro-Magnetic Field) generator is installed on the dredger(20,000HP) and through monitored flow status , dredging soil flow rate and sampled material specification is confirmed. Also dredger operating condition is measured and dredger power for soil transportation, hydraulic gradient and flow rate are compared, as transportation efficiency is calculated by this parameter, it is possible to check transportation efficiency improvement depending on each dredged soil material under electro-magnetic field. To verify the technique of dredged soil transfer using electromagnetic field, which is the core technique of the high efficiency dredged soil transfer, and the technique of expert system for pipeline transfer and the flow state. This could lead to a verification of transfer efficiency according to the characteristics of the dredged soil (sand, clay, silt) and the transfer distance (5km, 10km, 15km), which is planned to be used for a technology development of pump power reduction and long-distance transfer applying the high efficiency dredged soil transfer technology. KCI Citation Count: 0